CHARACTER OF RELIGIOUS MODERATION IN SHARIA MAQHASID REVIEW - Thoha Aufadin Zaka (MODERATIO: Jurnal Moderasi Beragama, 2021)
The understanding and practice of Islamic religious practice of Wasathiyah has several characteristics, namely Tawassuth (moderate), Tawazun (balanced), I'tidâl (straight and firm), Tasamuh (tolerant), Musawah (egalitarian and non-discriminatory), Aulawiyah (puts priority on priority). ), Tahaddhur (civilized), Tathawwur wa Ibtikar (dynamic, creative, and innovative). The concept is expected to be able to be applied in the life of the state and nation. So that this moderation concept will bring Indonesia to a better direction, so that there is no discrimination in diversity and creates a sense of security and comfort.